Tantangan Keamanan Informasi Pada Era Cloud Computing: Analisis Literatur Mengenai Strategi Kontrol dan Mitigasi Risiko - Imam Ariq Rizqy; Aril Sharon Saragih (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2026)
The development of cloud computing has transformed the way organizations stored, managed, and accessed information by providing more flexible and efficient technology services. At the same time, the adoption of this technology has introduced various information security challenges, including the risks of data breaches, unauthorized access, data loss, and increasingly sophisticated cyber threats. This study aimed to analyze the information security challenges in the era of cloud computing and to identify control strategies and risk mitigation measures based on a literature review. The study employed a qualitative approach using a literature review method by examining relevant scholarly articles, books, and academic publications. The findings indicated that securing cloud computing environments was not determined solely by the use of technology but also by the implementation of comprehensive controls, including identity and access management, data protection through encryption, continuous security monitoring, security auditing, and consistent risk management practices. In addition, increasing user awareness and implementing effective information security governance contributed to reducing potential threats and strengthening the protection of information assets. The study concluded that the combination of technical controls, organizational policies, and continuous risk management played a crucial role in maintaining the confidentiality, integrity, and availability of information within cloud computing environments.